The history of Canadian rock 'n' roll - Mersereau, Bob, 1960- (Backbeat Books, 2015)
Rock and roll was born in the United States during the 1950s. Its popularity rapidly grew, spreading across the Atlantic to England. The Brits transformed rock, bringing it back to the States in a new form with the British Invasion. Since that time, the two countries have dominated headlines and histories, in terms of rock music. What's often forgotten in these histories is the evolution of Canadian rock 'n' roll during the same period. Over the years, a huge contingent of Canadian artists has made invaluable contributions to rock 'n' roll. The list of innovative Canadian artists is quite impressive: Neil Young, Joni Mitchell, Paul Anka, Arcade Fire, The Band, Bryan Adams, Rush, Leonard Cohen, Celine Dion, Diana Krall, Gordon Lightfoot, Sarah McLachlan, Alanis Morissette, Tegan and Sara, Feist, Nickelback, and many others. The troop of all-star producers is equally impressive - Daniel Lanois (U2, Bob Dylan, Peter Gabriel), Bob Rock (Metallica, Aerosmith, Bon Jovi), Bob Ezrin (Pink Floyd, Alice Cooper, Kiss), and David Foster (Michael Jackson, Celine Dion). Canada's rock evolution is a lively, entertaining, and largely untold tale. Bob Mersereau presents a streamlined, informative trip through the country's rich history and depth of talent, from the 1950s to today, covering such topics as: Toronto's club scene, the folk rock and psychedelic rock of the 1960s, Canadian artists who hit major stardom in the United States, the challenges and reform of the Canadian broadcasting system, the huge hits of the 1970s, Canadian artists' presence all over the pop charts in the 1990s, and Canada's indie-rock renaissance of the 2000s.